Effects of BNP and Sacubitrilat/Valsartan on Atrial Functional Reserve and Arrhythmogenesis in Human Myocardium - Primessnig, Uwe; Deißler, Peter M.; Wakula, Paulina; Tran, Khai Liem; Hohendanner, Felix; von Lewinski, Dirk; Blaschke, Florian; Knosalla, Christoph; Falk, Volkmar; Pieske, Burkert; Grubitzsch, Herko; Heinzel, Frank R. (Frontiers in Cardiovascular Medicine, 2022)
Background: Although the angiotensin-receptor neprilysin inhibitor sacubitril/valsartan started a new era in heart failure treatment, little is known about the tissue-level effects of the drug on the atrial myocardial functional reserve and arrhythmogenesis. Methods and Results: Right atrial (RA) biopsies were retrieved from n=42 patients undergoing open-heart surgery and functional experiments were conducted in n=101 muscle strips. BNP did not modulate systolic developed force in human myocardium during β-adrenergic stimulation, but it significantly reduced diastolic tension (p<0.01) and the probability for arrhythmias (p<0.01). In addition, patient plasma NT-proBNP positively correlated with isoproterenol-induced contractile reserve in atrial tissue in vitro (r=0.65; p<0.01). sacubtrilat+valsartan (Sac/Val) did not show positive inotropic effects on atrial trabeculae function, but reduced arrhythmogeneity. Atrial and ventricular biopsies from patients with end-stage heart failure (n=10) confirmed that NEP is equally expressed in human atrial and ventricular myocardium. Right atrial NEP expression correlates positively with right atrial ejection fraction (r=0.806; p<0.05) and LV NEP correlates inversely with left atrial volume (r= -0.691; p<0.05). Conclusion: BNP ameliorates diastolic tension during adrenergic stress in human atrial myocardium, and may have positive long-term effects on the inotropic reserve. BNP and Sac/Val reduce atrial arrhythmogeneity during adrenergic stress in vitro. Myocardial NEP expression is downregulated with atrial remodeling suggesting a compensatory mechanism in heart failure.